Sustainable Living with Environmental Risks - Kaneko, Nobuhiro; Yoshiura, Shinji; Kobayashi, Masanori (Springer Japan : Imprint: Springer, 2014)
We are not free from environmental risks that accompany the development of human societies. Modern economic development has accelerated environmental pollution, caused loss of natural habitats, and modified landscapes. These environmental changes have impacted natural systems: water and heat circulation, nutrient cycling, and biodiversity. These changes in natural systems degrade ecosystem services and subsequently increase environmental risks for humans. Environmental risks, therefore, are not only human health risks by pollution, climatic anomalies, and natural disasters, but also degradation of ecosystem services on which most people are relying for their lives. We cannot entirely eliminate the risks, because it is not possible to attain zero impact on the environment, but we need to find a mechanism that minimizes environmental risks for human sustainably. This is the idea of the interdisciplinary framework of "environmental risk management" theory, which advocates harmony between economic development and environmental conservation. Based on this theory, the Sustainable Living with Environmental Risk (SLER) programme, adopted by the Japanese Ministry of Education (MEXT) as one of its strategic programmes, has been training graduate students at the Yokohama National University, Japan, from 2009 to 2013 to become future environmental leaders who will take the initiative in reducing the level of environmental risks and in protecting natural resources in the developing nations of Asia and Africa. This book provides students and teachers of this new academic field with a comprehensive coverage of case studies of environmental risks and their practical management technologies not only in Japan but also in developing nations in Asia and Africa.